Viewing research assessment, the academic reward system, and academic publishing through the power/knowledge lens of Foucault - Bowman, Timothy D. (Frontiers in Research Metrics and Analytics, 2023)
The academic research assessment system, the academic reward system, and the academic publishing system are interrelated mechanisms that facilitate the scholarly production of knowledge. This article considers these systems using a Foucauldian lens to examine the power/knowledge relationships found within and through these systems. A brief description of the various systems is introduced followed by examples of instances where Foucault’s power, knowledge, discourse, and power/knowledge concepts are useful to provide a broader understanding of the norms and rules associated with each system, how these systems form a network of power relationships that reinforce and shape one another.